INTRAOPERATIVE PROTECTIVE LUNG VENTILATION STRATEGIES AND POSTOPERATIVE PULMONARY COMPLICATIONS IN PATIENTS WITH COPD: A SYSTEMATIC REVIEW - Ruth Haryanti; Ripka Margaretha Ponggele (PT. Hasba Edukasi Mandiri, 2026)
Background: Patients with chronic obstructive pulmonary disease (COPD) undergoing elective surgery under general anesthesia carry an elevated risk of postoperative pulmonary complications (PPCs). Evidence on optimal intraoperative ventilation strategies in COPD-specific populations remains limited. Methods: A systematic review following PRISMA 2020 guidelines was conducted. PubMed, Scopus, and the Cochrane Library were searched from January 2015 to January 2025. Eligible study designs included randomized controlled trials, prospective cohort studies, and retrospective cohort studies reporting intraoperative ventilation strategies and postoperative pulmonary outcomes in adult COPD patients undergoing elective surgery. Methodological quality was assessed using the Newcastle-Ottawa Scale and Cochrane Risk of Bias 2.0 tool. Results: From 1,101 identified records, 220 duplicates were removed. After screening 881 records by title and abstract, 15 underwent full-text review and 4 studies were included, comprising 709 patients across 1 randomized controlled trial and 3 retrospective cohort studies. Low tidal volume ventilation reduced PPC risk (OR 0.50; p = 0.010). PEEP showed no significant protective effect. Dexmedetomidine reduced ICU admission rates (4% vs 28%; OR 9.33). One-lung ventilation exceeding 2 hours independently increased pulmonary infection risk. Ninety-day mortality was higher in patients who developed PPCs (5.8% vs 1.3%; p = 0.016). Conclusion: Low tidal volume ventilation reduces PPCs in COPD patients undergoing general anesthesia, whereas PEEP confers no significant benefit. Multimodal strategies including sugammadex reversal and intraoperative dexmedetomidine offer complementary risk reduction. Randomized trials in diverse COPD populations are needed.